1990
DOI: 10.1002/jnr.490270108
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of rat hippocampal neurons induced by estrogen in vitro: Effects on neuritogenesis and Na,K‐ATPase activity

Abstract: To gain insight into the mechanisms responsible for differentiation of hippocampal neurons growing in vitro, the effects of estrogen on neuritic development and on activity and distribution of isoforms of the Na, K-ATPase, were evaluated. Dissociated cells from hippocampi of 19-day-old rat fetuses were raised for 5 days in the presence or absence of 100 nM estradiol-17 beta (E2) in minimum essential medium supplemented either with 10% untreated fetal calf serum (MEM-10) or with 10% fetal calf serum previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 40 publications
4
37
2
Order By: Relevance
“…Our results showing that both the frequency distribution curves of dendritic length and the generalization of E2 effects to neurons with and without sP suggest that the action of E2 is exerted in the all neurons present in the cultures. This assumption is supported by similar findings in cultures of hippocampal (Blanco et al, 1990), hypothalamic (Diaz et al, 1992;Ferreira and Caceres, 199 I), and mesencephalic (Engele et a]. , 1989) neurons.…”
Section: Effect Of Estrogensupporting
confidence: 66%
“…Our results showing that both the frequency distribution curves of dendritic length and the generalization of E2 effects to neurons with and without sP suggest that the action of E2 is exerted in the all neurons present in the cultures. This assumption is supported by similar findings in cultures of hippocampal (Blanco et al, 1990), hypothalamic (Diaz et al, 1992;Ferreira and Caceres, 199 I), and mesencephalic (Engele et a]. , 1989) neurons.…”
Section: Effect Of Estrogensupporting
confidence: 66%
“…In addition, progesterone also blocked estrogen-induced sprouting, consistent with previous reports in which progesterone blocks estrogen's induction of hippocampal dendritic spine density. 80 It is not known whether these effects are due to direct action of estrogen on neurons, which could occur at several levels: activational, 79 trophic, 4,11,76 and protective (including anti-oxidant and anti-inflammatory). 11 Alternatively, indirect effects include those on glia.…”
Section: Discussionmentioning
confidence: 99%
“…Such rapid estrogen effects have been described for several neuronal phenotypes (Wong et al 1996). Particularly hippocampal cells appear to be targets for nonclassical estrogen action and it was suggested that rapid estrogen effects affect neuronal plasticity in the hippocampus (Gould et al 1990;Blanco et al 1990;Woolley 1999).…”
Section: Introductionmentioning
confidence: 98%
“…Gonadal steroids, i.e., estrogen, are well known to influence the activity and excitability of hippocampal neurons (Maggi and Perez 1985;Teyler et al 1980). In addition, there is emerging evidence that estrogen exerts a profound influence on the differentiation and plasticity of hippocampal neurons (Blanco et al 1990; Gould et al 1990). It is noteworthy that the structure of the hippocampus has a sexually dimorphic organization and that animal behaviors which are under hippocampal control differ between males and females (Beatty 1984;Juraska et al 1985;Loy 1986;Reisert et al 1996).…”
Section: Introductionmentioning
confidence: 98%